(untitled) (مجلة جامعة بابل للعلوم الانسانية, 2019)
Language is one of the most important pillars of human life and existence. It is the instrument of understanding and expression of the feelings and emotions that surround it. God has given it to man to be the primary means of building his life and society. This is the natural tool for the members of society to reveal what they think. And communication, this indicates its important social role. The Arabic language is the language of the Holy Quran, the national language of the people of the Arab nation, to which all Arabs are proud and proud, and which depend on them in the collection of information and therefore must take the first place in education. In spite of the many factors that intertwine and lead to this apparent weakness in the expression, but one of the important reasons in the view of the researcher due to the lack of care of teachers in the detection of the effectiveness of the use of teaching models proved to be sufficient in teaching, all prompted the researcher to conduct his current study The use of the Thilin model in the teaching of expression and the detection of its impact in expression performance, which contributes to the treatment or mitigate the problem, to serve our Arabic language. In order to achieve the goal of the research, the researcher randomly selected Al-Fayhaa prep school for boys. In the random sampling method, he chose (B) to represent the experimental group that taught the expression in the Thilin model, and (A) represents the control group that studies the expression in the traditional way. (33) students in each group. The researcher conducted an equivalence between the students of the two groups in the following variables: (the age of time calculated in months, their performance in expression,). The researcher identified the subjects studied during the period of the experiment after presenting them to a group of experts and specialists. The researcher prepared teaching plans for the subjects to be taught during the period of the experiment and the researcher presented two model plans to selected experts and specialists to determine their validity and relevance. The researcher studied the two groups of research during the period of the experiment and after the end of the experiment, the researcher applied the expression performance test to the students of the two groups. The researcher used the following statistical methods: (Z-Test) for two independent samples, Pearson correlation coefficient, and after analyzing the results, the researcher reached the following: 1.The students of the experimental group who studied the expression material using the thilin model were superior to the control group students who studied expression in the traditional way in the expressive performance test. The researcher concluded that the students responded to the Thilin model in teaching and interacted with him and the results showed that. The researcher concluded a set of recommendations: 1. The Thilin model should be used in teaching expression, because it has a role in improving expression. 2. The importance of teaching the expression should be given special importance in proportion to the place of expression among the branches of the other Arabic language and not to convert it to another lesson for another branch of Arabic or another lesson for a subject other than Arabic. He suggested the following: 1.Conduct a similar study on the fourth grade students in the expression, because the current research was limited to students Conducting a similar study to investigate the effect of the Thilin model in the development of creative thinking among students of the fourth literary.